Towards a Social Semiotic Approach of the Analysis of Emotion in Sound and Music - Machin, David (Public Journal of Semiotics, 2011)
This paper explores the possibility of a social semiotic approach to popular music in order to document the voice qualities, melodies and instrumental sounds found in popular music using the case study of Michael Jackson’s ‘Billie Jean’. The paper explores how these semiotic features, as well as the lyrics, communicate and reveal something of the subjectivity, the emotional world, created by musicians. Here the analysis explores Jackson’s use of restricted pitch ranges, breathiness, melodic patterns and gentle disjunctive articulation showing how these help to communicate the ‘tension’, and ‘trouble’ in the song. Taking a social semiotic approach the paper identifies the underlying available repertoire of meanings available to musicians and shows how musicians can skilfully draws upon these.